The Potential CC16 (Clara Cell Protein 16) as Biomarkers of Lung Damage in COVID-19 Survivors: Literature Review - Fika Tri Anggraini (Universitas Islam Negeri Sumatera Utara, Medan, 2022)
CC16 or Clara cell secretory protein-16 is a protein produced from the secretion of respiratory epithelial club cells, especially in the lungs. CC16 in several studies has anti-inflammatory effects and plays an important role in potential biomarkers and pathogenesis of chronic lung damage. One of the main respiratory diseases that attacks the lungs is COVID-19 (Coronavirus disease 2019). COVID-19 survivors had significantly decreased serum CC16 levels. The purpose of this review is to draw conclusions based on findings based on research results on the potential of CC16 as a biomarker of lung damage in COVID-19 survivors. This research used a literature review of research published from 2019-2023 in electronic media, such as ProQuest, Science Direct, CINAHL, and Pubmed. The number of Randomized controlled trials (RCTs) research articles obtained was seven articles that met the criteria. The research subjects of the study involved COVID-19 survivors. The keywords used Clara cell secretory protein-16 (CC16), a biomarker of lung damage, and COVID-19 survivor. They revealed that serum CC16 levels were found to be a potential damage or biomarker of lung disease in COVID-19 survivors. This review concluded that CC16's structure and the possible formation of mechanisms molecular and cellular can inhibit inflammation and in clinical applications are thought to be potential biomarkers and therapeutic targets of respiratory disease or chronic lung damage. Future research is required to investigate this hemoprotein in the circulation of COVID-19 survivors.Keywords: Biomarker, CC16, COVID-19 survivors, Clara cell protein-16